KONVERSI AGAMA DAN DINAMIKA KEIMANAN DALAM PERSPEKTIF PSIKOLOGI AGAMA - Rafik Ramdani; Sabrina Septiani; Nurrahman Ramadhan; Muhammad Aly Fadillah (STKIP Subang, 2026)
This study aims to analyze the phenomenon of religious conversion and the dynamics of faith from a psychology of religion perspective. The study focuses on the definition and concept of religious conversion, the factors influencing conversion, and the dynamics of faith experienced by individuals after conversion. This study uses a qualitative approach with library research. Data were obtained from various sources, such as books, journal articles, and scientific papers relevant to the topics of religious conversion and the psychology of religion. Data analysis techniques were conducted through descriptive and interpretive analysis of the sources studied. The results of the study indicate that religious conversion is a process of belief change that is not only formal, but also involves profound psychological transformation in the cognitive, affective, and behavioral aspects of religion. This process is influenced by various factors, including psychological factors such as inner crisis and the search for meaning in life, social factors such as the environment and interaction with the religious community, and spiritual factors in the form of profound religious experiences. The dynamics of faith after conversion are characterized by a process of self-adjustment, strengthening of faith, and internalization of religious values ​​in daily life. Thus, religious conversion is a continuous process of spiritual transformation and requires appropriate guidance and mentoring.